(3GdcGaj aj abg GdTjYIs - (3eMeO Hf jYbhH Hf ESMGb, CHh LYaQ Gdcdjfj,J (B329 (3g` s
(3ChdgG (B:s
(3ef Chd GdWgGQI s
(3BNQgG (B:s
(3BNQ cJGH GdeYjTI s
(3GdfSNI HgG MhGTs
(3LRA ef GdeNWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B145s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B15 - (3U (B337 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis